Response latencies of neurons in visual areas MT and MST of monkeys with striate cortex lesions. - Azzopardi, P; Fallah, M; Gross, C; Rodman, H (2003)
Cortical area, MT (middle temporal area) is specialized for the visual analysis of stimulus motion in the brain. It has been suggested [Brain 118 (1995) 1375] that motion signals reach area MT via two dissociable routes, namely a 'direct' route which bypasses primary visual cortex (area, striate cortex (V1)) and is specialized for processing 'fast' motion (defined as faster than 6 degrees/s) with a relatively short latency, and an 'indirect' route via area V1 for processing 'slow' motion (slower than 6 degrees/s) with a relatively long latency. We tested this proposal by measuring the effects of unilateral V1 lesions on the magnitudes and latencies of responses to fast- and slow-motion (depicted by random dot kinematograms (RDK) ) of single neurons in areas MT and medial superior temporal area (MST) of anaesthetized macaque monkeys. In the unlesioned hemisphere contralateral to a V1 lesion, response magnitudes and latencies of MT neurons were similar to those previously reported from MT neurons in normal monkeys, and there was no significant association between slow movement and long response latency (>100 ms), or between fast movement and short latency (< or =100 ms). V1 lesions led to diminished response magnitudes and increased latencies in area MT of the lesioned hemisphere, but did not selectively abolish MT responses to slow moving stimuli, or abolish long-latency responses to either slow- or fast-moving stimuli. Response magnitudes and latencies in area MST, which receives visual inputs directly from area MT and is also specialized for visual analysis of motion, were unaffected by V1 lesions (though we have shown elsewhere that directionally-selective responses in both areas were impaired by V1 lesions). Overall, the results are incompatible with the hypothesis that there are dissociable routes to MT specialized for processing separately fast and slow motion.